2013
DOI: 10.1002/14651858.cd004803.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Retention versus sacrifice of the posterior cruciate ligament in total knee arthroplasty for treating osteoarthritis

Abstract: The methodological quality and the quality of reporting of the studies were highly variable. With respect to range of motion, pain, clinical, and radiological outcomes, no clinically relevant differences were found between total knee arthroplasty with retention or sacrifice of the posterior cruciate ligament. Two statistically significant differences were found; range of motion was 2.4 ° higher in the posterior cruciate ligament sacrificing group, however results were heterogeneous; and the mean functional Kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 61 publications
4
73
1
3
Order By: Relevance
“…From a Cochrane systematic review and a recent meta-analysis on this topic [13,24], this greater flexion would be in concordance with an increased ROM seen in patients who use a PS design compared with a PCR design. However, little is known about whether this observed increase in flexion in the PS design after TKA is also expressed during walking, one of the most routine daily activities.…”
Section: Introductionmentioning
confidence: 61%
“…From a Cochrane systematic review and a recent meta-analysis on this topic [13,24], this greater flexion would be in concordance with an increased ROM seen in patients who use a PS design compared with a PCR design. However, little is known about whether this observed increase in flexion in the PS design after TKA is also expressed during walking, one of the most routine daily activities.…”
Section: Introductionmentioning
confidence: 61%
“…On the other side, in 2012, Li et al [14] in a meta-analysis of randomized controlled trials, compared the 2 types of knee prosthesis and reported similar outcomes in postoperative knee pain, function, complications and prosthesis survivorship. Finally, the meta-analysis of randomized and quasi-randomized controlled trials by Verra et al [15] in 2013, confirmed that there was no difference between posterior-stabilized and posterior-retained TKA regarding pain, and clinical and radiological outcomes, despite the fact that the range of motion and Knee Society Score were found higher with the former type.…”
Section: Retaining Tkamentioning
confidence: 91%
“…Verra et al [15] Meta-analysis of randomized and quasi-randomized controlled trials, comparing retention with sacrifice of the PCL in primary TKR…”
Section: Ref Type Of Study Outcomementioning
confidence: 99%
“…no clinical superiority of one type has been proven in the past, and overall survival for both types of prostheses is good [27].…”
Section: Introductionmentioning
confidence: 99%